The Effect of Competence on Student Readiness in the World of Work with Confidence as the Intervening Variable - Saputra, Rendy; Rosita, Sry; Chairunnisa, Fitri (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The study aims to determine the effect of competence on student readiness in the face of the work world or known as the work readiness with confidence as an intervening variable. The target of this research is on Merdeka Belajar Kampus Merdeka (MBKM) Students Strata 1 Management Studies Program of Faculty of Economics and Business Universitas Jambi. Population and sample for this study were MBKM students amounting to 190 students with the number of samples 66 students. This research is a quantitative research, the data used in this study obtained through the questionnaire method is composed. Methods of data analysis This research is descriptive statistical analysis using Structural Equantion (SEM) technique, with Partial Least Square (PLS) as a process of priority using the SmartPLS program (v.3.3.9). The results of this study prove that the competence has a positive and significant effect on the readiness of work, competence has a positive and significant influence on confidence, confidence has a positive and significant influence on work readiness, competence has positive and significant purses on work readiness through MBKM Student Strata 1 State of Management Studies Faculty of Economics and Business Universitas Jambi